Baroclinic Sea Level - James C. McWilliams; M. Jeroen Molemaker; Pierre Damien (Journal of Advances in Modeling Earth Systems, 2024)
Abstract Sea level and its horizontal gradient are an expression of oceanic volume, heat content, and currents. Large‐scale currents have historically been viewed as mostly “baroclinic,” and tides as “barotropic,” respectively, in the loose sense of being strongly related to the oceanic density distribution or not. In particular, the evolution of the barotropic velocity is influenced by a horizontal pressure‐gradient force that depends on the gradient of a particular depth‐weighting of the density field as well as on the gradient of the sea‐surface elevation ζ; hence, even the tides must be viewed as a product of the coupled interaction of barotropic and baroclinic fields. The purpose of this note is to give dynamical precision to the distinction between barotropic and baroclinic contributions to ζ and the surface pressure‐gradient force −g∇ζ, and, in the particular case of the tides, demonstrate their combined barotropic‐baroclinic interactions with a realistically forced, high‐resolution simulation of the Pacific Ocean circulation. While the different tidal sea‐level contributions manifest a horizontal scale separation (e.g., more barotropic at larger scales; more baroclinic surface pressure‐gradient force at smaller scales), there are cross‐mode corrections in both at the level of tens of percent. The proposed barotropic‐baroclinic decomposition is generally relevant to the sea‐level expression of oceanic currents.